'The constitution of political membership': Punishment, political membership, and the Italian case. (November 2017) - Gallo, Zelia
The article argues that punishment will vary depending on how political membership is constituted in different polities. This has significant implications for arguments that link contemporary western punitiveness to 'anti-politics', understood here as a degradation of political membership. The article argues that the spread of 'anti-politics' and its penal implications will depend on how political membership is constituted in different polities and in their 'State'. It reaches this conclusion by exploring the way in which 'the State' appears in the literature on politics and punishment, and by adopting a re-worked definition of 'the State'. The Italian case study is then used to demonstrate both the link between punishment and political membership, and the need to contextualize our analyses of 'anti-politics' and punitiveness.